Flavonoids: biological activities, nutritional and immunological aspects, therapeutic potential, food applications, and human health benefits—A comprehensive review - Mohamed T. El-Saadony; Ahmed M. Saad; Mohamed A. Fahmy; Dina Mostafa Mohammed; Dina Khodeer; Esmael M. Alyami; Samar Sami Alkafaas; Mthokozisi Dladla; Soumya Ghosh; Mohammad A. A. Al-Najjar; Synan F. AbuQamar; Khaled A. El-Tarabily (Frontiers in Nutrition, 2026)
The global burden of infectious and non-communicable diseases presents a critical challenge, highlighting the urgent need for novel, safe, and effective therapies. Bioactive compounds from medicinal plants, especially flavonoids, offer a promising resource for drug discovery due to their diverse and potent pharmacological effects documented in preclinical studies. This comprehensive review summarizes current knowledge of flavonoids, including their classification into 14 main groups and their production via biosynthesis, chemical synthesis, modification, and extraction. While structural modification remains a key aspect of drug development, biosynthesis is increasingly seen as a potential transformative strategy for sustainable large-scale production. However, it requires a deeper understanding of metabolic pathways and optimization of synthetic methods. Aside from production challenges, a major translational hurdle is the inherently low bioavailability of many flavonoids. This review critically examines innovative solutions under investigation, such as advanced nanoparticles and colloidal drug delivery systems designed to address challenges in solubility, stability, and absorption. It also summarizes the current understanding of the mechanisms of action underlying their broad biological activities, primarily as evidenced by preclinical models, including nutritional, immunological, and disease-specific effects, and discusses potential drug interactions warranting clinical attention. Lastly, the review highlights key research gaps, including the need for more robust in vivo validation, standardized extracts to improve reproducibility, and well-designed clinical trials to verify efficacy in humans. Future directions include leveraging metabolic engineering and artificial intelligence to optimize biosynthesis, as well as targeted clinical studies of advanced delivery systems. By integrating these approaches, this review aims to establish a framework for ongoing research on flavonoids to inform future translational efforts that may eventually support their development as clinical therapies.